A importância dos fatores estruturais na garantia da segurança alimentar na produção de refeições para escolares - Correia, Maria João (2012)
The design of school canteens shall be subject to detailed studies regarding its functional and operational activity. It must consider several factors such as legal aspects, production technical requirements, architectural and working conditions as well as economic aspects in order to guarantee the correct and safe supply of the meals. In addition to literature review some technical visits were done to allow the on-site checking of the fulfilment of the several factors considered. Several structural nonconformities were identified that affect compliance with the good manufacturing practices. Most of them could have been avoided if, at the design stage of the project, these factors had been considered. It would be useful to ensure that the different technicians involved in food service, namely nutritionists, participate in multidisciplinary meetings to evaluate base plans, and program briefs in order to achieve a better project proposal.